Renal salt wasting as part of dysautonomia in Guillain-Barré syndrome - Lenhard, Thorsten; Grimm, Christiane; Ringleb, Peter A. (Journal of neurology, neurosurgery, and psychiatry, 2011)
Cerebral salt-wasting syndrome and the syndrome of inappropriate antidiuresis (SIAD) are the most important causes of non-iatrogenic hyponatraemia that can significantly complicate various brain diseases. Salt wasting without an underlying CNS disease may have been disregarded so far by clinicians and has been described as renal salt-wasting (RSW) in patients as drug side effect (eg, cisplatin), in older people with various common diseases (eg, hip fracture, pulmonary infections) and other sporadic conditions. In Guillain-Barré Syndrome (GBS), however, hyponatraemia has been described mainly as SIAD. However, symptoms of hyponatraemia rarely develop in GBS. Here, we report on a woman with GBS with dominant symptoms of dysautonomia and moderate severe hyponatraemia. We could identify RSW as part of the autonomic dysfunction that significantly contributed to disease worsening.